2018
DOI: 10.2298/tsci170530122d
|View full text |Cite
|
Sign up to set email alerts
|

The study of effects of greenery on temperature reduction in urban areas

Abstract: Urban landscape is largely characterized by high degree of built space, high share of artificial surface material and the reduction of green areas, which leads to changes in the microclimate and the deterioration of thermal comfort in outdoor urban space. One of the most important roles of urban greenery is the impact on the reduction of air temperature due to less heating of green space compared to paved surfaces and due to tree shading. The paper analyses the influence of urban greenery on temperature reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Massive infrastructural development increases the proportion of impervious and paved surfaces, which retained more energy and radiated more heat [ 65 , 66 ]. On the other hand, green space consists of penetrable layers and emitted less heat due to tree shading, which helps to reduce the heat [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…Massive infrastructural development increases the proportion of impervious and paved surfaces, which retained more energy and radiated more heat [ 65 , 66 ]. On the other hand, green space consists of penetrable layers and emitted less heat due to tree shading, which helps to reduce the heat [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to the results of the study of Ðekić et al [72], a distinct variation between the temperatures of various surfaces in UGSs was identified, particularly in the high solar radiation hours-around noon. More specifically, they found that the temperature difference between the grass surface (coolest) and the dark asphalt varied between 9 and 19.7 • C, whereas in our study it was on average 16.3 • C. In addition, Ðekić et al [72] also observed a difference of 10-24.5 • C between the hottest surface temperature and that of the ambient air, a range that is in line with the findings of our study where the respective difference between the asphalt and the ambient air temperature, measured by the meteorological station, was 18.2 • C. Similarly, Ðekić et al [72] mention that for the hotter period of measurements (mid-July to mid-August) the average maximum temperature for all artificial surfaces was well above 50 • C (average 52.1 • C in our study for all artificial materials ranging from 49.6 • C for the internal paved corridors to 54.4 • C for asphalt), while the grass-covered area more or less matched the temperature of the ambient environment, which is also in line with our study, since the temperature differences of grass and shrubs against ambient air temperature measured by our station were very close (38.0-35.8 • C and 36.7-36.1 • C, respectively.…”
Section: Temperature Attributesmentioning
confidence: 99%
“…C. Relation to landscape Landscapes or green areas can make buildings cooler and also the aesthetic purposes (Diana et al, 2021). Vegetation affects room temperature regulation because it has a cooling (Dekić et al, 2018). The shade from the tree helps lower temperatures and reduces energy use (Dekić et al, 2018).…”
Section: B Transitional Spacementioning
confidence: 99%
“…Vegetation affects room temperature regulation because it has a cooling (Dekić et al, 2018). The shade from the tree helps lower temperatures and reduces energy use (Dekić et al, 2018). Based on figure 3.5, landscape area of this building has less green area.…”
Section: B Transitional Spacementioning
confidence: 99%